Optimization Olive Oil Extraction by Pre-heat Treatment Olive Fruits - Walid M. Al-Rousan (Advance Journal of Food Science and Technology, 2017)
The present investigation was conducted on the aim to determine the optimum pre-heat treatment (temperature and time) for olive fruits, at early stages of maturity, in order to enhance oil extraction. The heat treatment was performed of two Jordanian cultivars ＂NabaliBaladi＂ (NB) and ＂NabaliMuhassan＂ (NM) by dipping the olive fruits in heated water at 50, 55, 60 and 65°C, for 2, 3 and 4 minutes at each heating temperature. Olives are then coarsely ground in fruit mill, the olive paste pressed in hydraulic press at 120 k N/cm^2 for 45 min and finally the oil-water mixture was centrifuged to separate oil. On the basis of results obtained, the yield of oil was significantly (p≤0.05) increased, the increase for NB ranged 0.2-4.0% and the optimum heat treatments were 55℃/ 3-4 min and 60℃/ 2-3 min, while the increase for NM ranged 0.6-3.8% and the optimum heat treatment was 60 ℃/ 3-4 min. The acidity of oils obtained with pre-heat treatment had slightly improved, while there were some adverse effect regarding peroxide values, UV absorption, oxidative stability and sensory evaluation. Phenolic compounds and α-tocopherols contents significantly decreased, but their values were within the legal limits. The chlorophyll pigment intensity increased significantly in the extracted oil through raising pre-heat treatment of olives, the increase was 3.6-fold and 2.8-fold of NB and NM, respectively, compared to the olive oil control, where the rise of carotene was 2.5-fold in both varieties. These results conclude that pre-heat treatment processing is beneficial for quantity and quality of olive oil produced.